Implementasi Program Pembinaan Karakter Siswa di SMP Muhammadiyah 01 Medan - Azhari, Jana (Universitas Labuhanbatu, 2023)
Character education is one of the keys to the success of education in Indonesia. The government's attention to the character of education is not something new, but rather places education in its true proportions, because in the future the Indonesian nation will be held by generations who are currently still at the educational level. Character education is important to present in every educational activity so that it can produce individuals who have good character.. The lack of character education has an impact on the nation's future generations who face quite serious challenges, especially for the character education of the Indonesian nation. This research was conducted with the aim of obtaining information regarding the Implementation of the Character Development Program at SMP Muhammadiyah 1 Medan. This research uses a qualitative descriptive approach, namely research conducted based on surveys according to conditions occurring in the field. Data collection tools using interview techniques, observation and documentation. Based on the research results, it can be concluded that the application of Islamic religious education values through character training programs by implementing congregational prayers, morning assembly, evening worship, tahsin recitations, Muhammadiyah Student Association (IPM), flag ceremonies, tadabbur alam, fardhu kifayah, and infaq friday is very good at shaping student character through character training activities that are carried out repeatedly.